Intracellular Modulation of Signaling Pathways by Annexin A6 Regulates Terminal Differentiation of Chondrocytes - Minashima, Takeshi (American Society for Biochemistry and Molecular Biology, 2012)
Annexin A6 (AnxA6) is highly expressed in hypertrophic and terminally differentiated growth plate chondrocytes. Rib chondrocytes isolated from newborn AnxA6−/− mice showed delayed terminal differentiation as indicated by reduced terminal differentiation markers, including alkaline phosphatase, matrix metalloproteases-13, osteocalcin, and runx2, and reduced mineralization. Lack of AnxA6 in chondrocytes led to a decreased intracellular Ca(2+) concentration and protein kinase C α (PKCα) activity, ultimately resulting in reduced extracellular signal-regulated kinase (ERK) and p38 mitogen-activated protein kinase (MAPK) activities. The 45 C-terminal amino acids of AnxA6 (AnxA6(1–627)) were responsible for the direct binding of AnxA6 to PKCα. Consequently, transfection of AnxA6−/− chondrocytes with full-length AnxA6 rescued the reduced expression of terminal differentiation markers, whereas transfection of AnxA6−/− chondrocytes with AnxA6(1–627) did not or only partially rescued the decreased mRNA levels of terminal differentiation markers. In addition, lack of AnxA6 in matrix vesicles, which initiate the mineralization process in growth plate cartilage, resulted in reduced alkaline phosphatase activity and Ca(2+) and inorganic phosphate (P(i)) content and the inability to form hydroxyapatite-like crystals in vitro. Histological analysis of femoral, tibial, and rib growth plates from newborn mice revealed that the hypertrophic zone of growth plates from newborn AnxA6−/− mice was reduced in size. In addition, reduced mineralization was evident in the hypertrophic zone of AnxA6−/− growth plate cartilage, although apoptosis was not altered compared with wild type growth plates. In conclusion, AnxA6 via its stimulatory actions on PKCα and its role in mediating Ca(2+) flux across membranes regulates terminal differentiation and mineralization events of chondrocytes.